Strong Response of Stem Photosynthesis to Defoliation in Mikania micrantha Highlights the Contribution of Phenotypic Plasticity to Plant Invasiveness - Zheng, Jin; Zhang, Tai-Jie; Li, Bo-Hui; Liang, Wei-Jie; Zhang, Qi-Lei; Cai, Min-Ling; Peng, Chang-Lian (Frontiers in Plant Science, 2021)
Phenotypic plasticity affords invasive plant species the ability to colonize a wide range of habitats, but physiological plasticity of their stems is seldom recognized. Investigation of the stem plasticity of invasive plant species could lead to a better understanding of their invasiveness. We performed pot experiments involving defoliation treatments and isolated culture experiments to determine whether the invasive species Mikania micrantha exhibits greater plasticity in the stems than do three non-invasive species that co-occur in southern China and then explored the mechanism underlying the modification of its stem photosynthesis. Our results showed that the stems of M. micrantha exhibited higher plasticity in terms of either net or gross photosynthetic rate in response to the defoliation treatment. These effects were positively related to an increased stem elongation rate. The enhancement of stem photosynthesis in M. micrantha resulted from the comprehensive action involving increases in the Chl a/b ratio, D1 protein and stomatal aperture, changes in chloroplast morphology and a decrease in anthocyanins. Increased plasticity of stem photosynthesis may improve the survival of M. micrantha under harsh conditions and allow it to rapidly recover from defoliation injuries. Our results highlight that phenotypic plasticity promotes the invasion success of alien plant invaders.